Is Maternal Guilt a Cross-National Experience? - Collins, Caitlyn (Qualitative sociology, 2021)
Many working mothers in the US say that they feel guilty about their inability to live up to cultural ideals of the “good mother” embedded in intensive mothering discourse. Intensive mothering is reflected in and exacerbated by the country’s work-family policies. The United States is an outlier among Western welfare states for its lack of policy supports for families, assuming that childrearing is a private responsibility even though most mothers work outside the home today. So how do working mothers outside of the US experience maternal guilt? Does a more family-friendly policy environment mitigate these feelings of guilt? Using detailed accounts of four women drawn from a larger interview study of 109 working mothers in Sweden, Germany, Italy, and the United States, I demonstrate how policy context does—and does not—make a difference in the experience of maternal guilt. A feeling of guilt helped to define “good mothers” across all four contexts. However, I found that public policy has a role to play in reducing maternal guilt in three specific ways: (1) by giving mothers more time outside of work, (2) encouraging fathers to complete more unpaid care work, and (3) distributing the responsibility and costs of childrearing more broadly.